International Consensus Guidelines for the Optimal Use of the Polymyxins: Endorsed by the American College of Clinical Pharmacy (ACCP), European Society of Clinical Microbiology and Infectious Diseases (ESCMID), Infectious Diseases Society of America (IDSA), International Society for Anti‐infective Pharmacology (ISAP), Society of Critical Care Medicine (SCCM), and Society of Infectious Diseases Pharmacists (SIDP)1. Issue 1 (2nd February 2019) - Tsuji, Brian T.; Pogue, Jason M.; Zavascki, Alexandre P.; Paul, Mical; Daikos, George L.; Forrest, Alan; Giacobbe, Daniele R.; Viscoli, Claudio; Giamarellou, Helen; Karaiskos, Ilias; Kaye, Donald; Mouton, Johan W.; et al.
Abstract : The polymyxin antibiotics colistin (polymyxin E) and polymyxin B became available in the 1950s and thus did not undergo contemporary drug development procedures. Their clinical use has recently resurged, assuming an important role as salvage therapy for otherwise untreatable gram‐negative infections. Since their reintroduction into the clinic, significant confusion remains due to the existence of several different conventions used to describe doses of the polymyxins, differences in their formulations, outdated product information, and uncertainties about susceptibility testing that has led to lack of clarity on how to optimally utilize and dose colistin and polymyxin B. We report consensus therapeutic guidelines for agent selection and dosing of the polymyxin antibiotics for optimal use in adult patients, as endorsed by the American College of Clinical Pharmacy (ACCP), Infectious Diseases Society of America (IDSA), International Society of Anti‐Infective Pharmacology (ISAP), Society for Critical Care Medicine (SCCM), and Society of Infectious Diseases Pharmacists (SIDP). The European Society for Clinical Microbiology and Infectious Diseases (ESCMID) endorses this document as a consensus statement. The overall conclusions in the document are endorsed by the European Committee on Antimicrobial Susceptibility Testing (EUCAST). We established a diverse international expert panel to make therapeutic recommendations regarding the pharmacokinetic and pharmacodynamic properties of the drugs and pharmacokinetic targets, polymyxin agent selection, dosing, dosage adjustment and monitoring of colistin and polymyxin B, use of polymyxin‐based combination therapy, intrathecal therapy, inhalation therapy, toxicity, and prevention of renal failure. The treatment guidelines provide the first ever consensus recommendations for colistin and polymyxin B therapy that are intended to guide optimal clinical use.